2017
DOI: 10.1002/adem.201700692
|View full text |Cite
|
Sign up to set email alerts
|

Spin Valve Effect of 2D‐Materials Based Magnetic Junctions

Abstract: The magnetotransport properties of spin valve structure are highly influenced by the type of intervening layer inserted between the ferromagnetic electrodes. In this scenario, spin filtering effect at the interfaces plays a crucial role in determining the magnetoresistance (MR) of such magnetic structures, which can be enhanced by using a suitable intervening layer. Here, the authors investigate the spin filtering effect of the two-dimensional layers such as hexagonal boron nitride (hBN), graphene (Gr), and Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…A fabrication of graphene-hBN van der Waals heterostructure has been further developing, and the creation of the graphene-hBN heterostructure has been possible 32 . Previous experimental study shows the use of graphene-hBN heterostructure as a tunnel barrier of 2D materials based MTJ and found an increasing performance compared with that of graphene or hBN based MTJs, as well as a unique inverted signal of the spin valve, have been found 33 . The unique chemical and physical properties are expected between the interface and insulator barrier.…”
Section: Introductionmentioning
confidence: 97%
“…A fabrication of graphene-hBN van der Waals heterostructure has been further developing, and the creation of the graphene-hBN heterostructure has been possible 32 . Previous experimental study shows the use of graphene-hBN heterostructure as a tunnel barrier of 2D materials based MTJ and found an increasing performance compared with that of graphene or hBN based MTJs, as well as a unique inverted signal of the spin valve, have been found 33 . The unique chemical and physical properties are expected between the interface and insulator barrier.…”
Section: Introductionmentioning
confidence: 97%
“…[ 69–71 ] Concept of spin filtering was also used for explanation toward reversed MR signals as recently discovered in molecular spin valves exploiting organic radical self‐assembled monolayer and 2D materials. [ 72–76 ] Since our negative MR response is contributed by bulk spin transport rather than spinterface engineering, we prefer to use “filtering‐like” term to define such spin reversal activity of bulk spin transport. This is the first report on such fascinating spin phenomenon in solution‐processed conjugated D–A polymers.…”
Section: Resultsmentioning
confidence: 99%
“…investigated the spin filtering effect of vertical magnetic tunneling junctions, i.e., Ni/h‐BN/Ni, Ni/graphene/Ni, and Ni/graphene–BN/Ni, respectively. [ 289 ] The magnetoresistance and spin polarization for h‐BN incorporated junction were 0.83% and 6.4%, while that of graphene junction were 0.16% and 2.8%. The results revealed that Ni/h‐BN junctions had higher spin filtering efficiency, compared with Ni/graphene junctions, as depicted in Figure 15h.…”
Section: Bn‐based Spin Valves and Magnetic Tunneling Junctionsmentioning
confidence: 99%